DESKRIPSI SISTEM PENDIDIKAN HINDU DALAM PEMBANGUNAN BUDI PEKERTI - Ni Putu Ratni (Jurnal PASUPATI, 2014)
Pasraman is Hindu Education System that had been developed and it has roots in Upanisad education system. The Study about Deskripsi Sistem Pendidikan Hindu dalam Pembangunan Budi Pekerti has purpose to find out about How this education system had been applied; and about how the connection of it with students manners development. The description made base on the study on the implementation of Pasraman education system in this modern era. As the result, we found out that this type of education had delivered big enough contribution to students’ manners development, especially the ones who were active participating in this non formal education. Pasraman is a form of Upanisad education system which has been developed; and has been collaborated with modern education system without ignoring primary Hindu education target, those are to strengthening the understanding and to strengthening the application of tattwa, susila, and upacara. That fact makes Pasraman become a big potential non formal Hindu education system in order to build and develop the students’ manners.